Surveillance strategies using routine microbiology for antimicrobial resistance in low and middle-income countries - Lim, C; Ashley, EA; Hamers, RL; Turner, P; Kesteman, T; Akech, S; Corso, A; Mayxay, M; Okeke, IN; Limmathurotsakul, D; Doorn, HRV (Elsevier, 2021)
Background: Routine microbiology results are a valuable source of antimicrobial resistance (AMR) surveillance data in low- and middle-income countries (LMICs) as well as in high-income countries. Different approaches and strategies are used to generate AMR surveillance data.